Impact response of sandwich composites with P-Aramid (Kevlar®) waste fibre reinforcement - Kaya, Gaye; Selver, Erdem; Dincer, Tebernus; Atici, Arzu (Wydawnictwo Politechniki Łódzkiej, 2022)
This work investigates the impact performance of sandwich composites made of polyurethane/p-aramid (Kevlar®, K129) fibre waste/paper cardboard core and Kevlar® fabric edge wastes face materials. Kevlar® waste fibres were added the core part at various weight ratios (2%, 5%, and 10%). Sandwich composites were performed under 50J, 100J and 200J to compare their impact resistance. Impact tests indicated that the addition of Kevlar® waste fibres increased the energy absorption capacities of sandwich composites compared to neat core sandwich composites. However, they showed lower impact force values due to distortion of cardboards during manufacturing of sandwich composites.
Keywords: sandwich composites; p-aramid fibres; waste fibres; impact response; kompozyty przekładkowe; włókna p-aramidowe; włókna odpadowe; reakcja na uderzenie